Vasopressina como terapia de resgate em choque séptico refratário à catecolaminas em pediatria - Dalcin, Tiago Chagas (2013)
Importance: In 2012, worldwide, there were more than 3.8 million deaths related to infectious diseases in children younger than five years old. The major concern is that pediatric infections often can evolve into septic shock, defined as infection in the presence of cardiovascular dysfunction. The treatment of septic shock has been based on antibiotic therapy, volume resuscitation and cardiocirculatory support by catecholamines. However, a proportion of patients develop refractoriness to catecholamines, with higher morbidity and mortality. Recently, vasopressin has been used as vasopressor in pediatric catecholamine-refractory septic shock. It is important the evaluation of the current state of evidence for the use of vasopressin in the pediatric septic shock, as well as the addition of new experiences with the use of vasopressin as a rescue-therapy in pediatric catecholamine-refractory septic shock. Objectives: The current dissertation has as objective i) summarize the evidences relating the use of vasopressin in the pediatric septic shock and ii) describe the experience of a Pediatric Intensive Care Unit (PICU) with the use of vasopressin as a rescue-therapy in catecholamine-refractory septic shock. Methods: Using MEDLINE, a review of the medical literature was made to find the scientific articles published in English (1966-August 2013), using vasopressin as vasopressor with septic shock patients included in the sample. Secondly, the five years of experience of a PICU with the use of vasopressin as rescue-therapy in children with catecholamine-refractory septic shock (norepinephrine ≥ 1μg/kg/min with variable doses of other inotropic/vasopressors) were evaluated. Using paired Student s t test, the blood pressure means and the modified vasoactive score means of the two hours prior (T-2) the use of vasopressin were compared with the means of the first 10 hours with (T10) vasopressin. Results: In the literature review, 16 case reports/series and one randomized controlled trial were found, with a total of 259 patients, from which 35,5% had septic shock. In all studies, vasopressin was related with the increase in blood pressure levels. Additionally, in the majority, it was related with the reduction of other vasopressors. The only benefit reported in the randomized controlled trial was the increase of mean blood pressure in the first hour of vasopressin use. The evaluation of the experience with vasopressin as rescue-therapy in refractory septic shock resulted in 16 patients, with a median initial dose of vasopressin of 0.0005 U/kg/min ([IQR] 0.00024-0.00168). The mean blood pressure and diastolic blood pressure increased with the use of vasopressin (p=0,0267; p=0,0194, respectively). An increase in the modified vasoactive scores was observed, which was unrelated to the blood pressure alterations. Conclusions: Currently, the evidences of the use of vasopressin in pediatric septic shock are scarce, suggesting its prudent use as rescue therapy in catecholamine-resistant shock with low systemic vascular resistance and high cardiac index. Specifically in the studied PICU, vasopressin increased the blood pressures, however without a spare effect on catecholamines